Multiparametric analysis in the peripheral blood of Giant Cell Arteritis and Polymyalgia Rheumatica patients at the early phases of steroid treatment reveals changes in cell subpopulations and lipid mediators: a preliminary study - Palamidas, Dimitris Anastasios; Papadaki, Maria; Paschalidis, Nikolaos; Pavlos, Eleftherios; Chatzis, Loukas; Palla, Panagiota; Argyropoulou, Ourania D.; Prevezanos, Dionysios; Dubourdeau, Marc; Kambas, Konstantinos; Galani, Ioanna Evdokia; Goules, Andreas V.; et al. (Frontiers in Immunology, 2025)
IntroductionGiant Cell Arteritis (GCA) and Polymyalgia Rheumatica (PMR) are autoimmune/autoinflammatory disorders presenting as acute inflammatory responses and are highly responsive to steroids. In this report, we aim to decipher the immune landscape including immune cell subpopulations, plasma cytokines, and small lipid mediators (LMs) at the very early stages of steroid treatment initiation in 4 distinct time points at: 0h (T1), 48h (T2), 96h (T3), and 24 weeks (T4).Patients and methodsSerum, plasma and peripheral blood mononuclear cells (PBMCs) were collected prospectively from 8 GCA and 6 PMR newly diagnosed patients. Sixteen healthy individuals served as controls (HC). Deep immunophenotyping by CyTOF was performed in PBMCs at T1-T3. A multiplex Luminex assay measured serum levels of 21 cytokines at T1 and T3. Levels of lipid mediators (LMs) were evaluated at T1, T3 and T4 with the LC-MS/MS method.ResultsTotal CD8+ T cells and DCs were decreased within 48–96 hours, following steroid treatment, while B-cells were increased at 48 hours. Further analysis of immune subpopulations containing the major cell types revealed different frequencies of distinct CD8+, CD4+, DCs, and B cell subtypes. Out of 21 cytokines/chemokines evaluated, only ITAC levels were decreased at T3. The ratio of pro/anti-inflammatory LMs was high at T1 in patients with either PMR or GCA. However, 6 months after steroid treatment it returned to normal in PMR patients, but remained high in GCA patients, providing the only discriminatory element between the two diseases.ConclusionThe rapid clinical improvement of GCA and PMR patients, following steroid treatment, is associated with immune cell type alterations, but it is poorly associated with plasma cytokine levels. Small lipid mediators can differentiate GCA and PMR patients. The persistently elevated levels of pro-inflammatory LMs might be related to the underlying residual tissue inflammation described in GCA. These preliminary results suggest that further studies in a larger patient cohort are required to validate these findings.